Masculinity, Carceral Discipline and the Gang Life - Iwilade, Akin (African studies (Johannesburg), 2025)
How do marginalised categories archive and narrate the self in contexts of carceral discipline? Drawing from an analysis of police crime diaries, court records and interviews from Lagos, Nigeria, this article explores the way gang members narrate the gang self while in detention. It asks how an autobiographic crafting that legislates the performance of vulnerability encounters a parallel process of self-making that incites the performance of masculine hardness. In short, how do gangsters seek to signal their masculinity when, in the context of arbitrary use of police power, being able to perform vulnerability and deception is so central to their chances of evading carceral discipline? The paper identifies three key narrative strategies - proximate distance, invisible man, and occult obscurities - as central to the nuanced and delicate autobiographical formulations that gang members deploy in order to satisfy the two seemingly contradictory urges. The article highlights the important role that vulnerability and its performance plays in the gang personae and demonstrates the need to recognise what this means for how we think of masculinity.